Pengaruh Independensi Auditor Terhadap Kualitas Audit - Lilis Karnita Soleha (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
This study aims to determine the magnitude of the influence of auditor independence on audit quality. The population in this study is the auditor who works on the KAP in Bandung. The sampling technique used purposive sampling method with 30 samples. Data analysis technique used is verificative analysis technique. Result of hypothesis test in this research show that auditor independence has positive and significant effect to audit quality equal to 55,60% and the rest is 44,40% influenced by another factor. To improve the quality of audits, the auditor in performing their duties independently without getting pressure from clients or parties so as to produce a quality audit.